Consequences of the impact of COVID-19 pandemic on breast cancer at a single Italian institution - Daniele Ugo Tari; Rosalinda Santonastaso; Fabio Pinto (Open Exploration Publishing Inc., 2022)
Aim: To evaluate the local impact of the coronavirus disease 2019 (COVID-19) pandemic on breast cancer (BC) care, with particular attention to the economical and psychological consequences of the possible delay of new diagnoses and treatments. Methods: Three years' activity (from 2019 to 2021) has been compared. The number of BCs diagnosed from the total amount of mammographic and ultrasound (US) examinations performed in women aged more than 40 years old has been considered. A Pearson's chi-squared test was performed to verify differences between results. Statistical significance was set at P ≤ 0.01. Results: A statistically significant difference was found in the number of BC diagnosed between screening and ambulatory care patients in both the 2019-2020 (χ2 = 24.93, P < 0.01) and 2019-2021 (χ2 = 29.93, P < 0.01) comparisons. No statistically significant difference was found in the data recorded between 2020 and 2021 (χ2 = 2.35, P > 0.01). By evaluating the specific age groups for each year, a statistically significant difference (P < 0.01) was found in the number of BC diagnosed in screening patients aged 50-69 years old in both 2019-2020 and 2019-2021 comparisons. The percentages of early BC diagnosed in 2019, 2020, and 2021 were 80.9%, 91.7%, and 89.8%, respectively. The adherence rates to screening in 2019, 2020, and 2021 were 67.5%, 45.2%, and 56.9%, respectively. Conclusions: Results showed a reduction of new diagnoses in the screening range during the pandemic in comparison with the previous period. The high percentage of early BC would seem to have prevented worsening outcomes. Nevertheless, women who have not undergone screening could present a more advanced stage disease in the following years. Consequently, the evaluation of possible solutions to guarantee an essential level of care with the purpose to avoid worsening patients' outcomes and the increase in healthcare costs is mandatory.